2012
DOI: 10.3899/jrheum.110923
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Esophageal Dysmotility in Systemic Sclerosis

Abstract: ED is more frequent in patients with dcSSc than in those with lcSSc, and is more likely to deteriorate over time. Given the potential associated risks of erosive esophagitis, Barrett's esophagus, and esophageal cancer in patients with SSc, routine screening and monitoring for ED is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…Symptoms include dysphagia, odynophagia, heartburn and regurgitation but patients can also present with other symptoms related to oesophageal reflux such as chronic cough, hoarseness, pharyngitis, laryngospasm or asthma. Although oesophageal involvement is present in both limited and diffuse SSc, a recent study concluded that oesophageal dysmotility is more common in patients with diffuse SSc and is more likely to deteriorate over time compared to patients with limited SSc . Another study that assessed oesophageal motor function by high‐resolution manometry found that severe oesophageal dysmotility is associated with longer duration of SSc and with the presence of interstitial lung disease .…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms include dysphagia, odynophagia, heartburn and regurgitation but patients can also present with other symptoms related to oesophageal reflux such as chronic cough, hoarseness, pharyngitis, laryngospasm or asthma. Although oesophageal involvement is present in both limited and diffuse SSc, a recent study concluded that oesophageal dysmotility is more common in patients with diffuse SSc and is more likely to deteriorate over time compared to patients with limited SSc . Another study that assessed oesophageal motor function by high‐resolution manometry found that severe oesophageal dysmotility is associated with longer duration of SSc and with the presence of interstitial lung disease .…”
Section: Resultsmentioning
confidence: 99%
“…Akin to our finding of an association with more severe skin disease assessed by MRSS and more pronounced esophageal dysmotility (i.e., absent contractility), Vischio et al . found a correlation between MRSS and abnormal esophageal transit scintigraphy . Dermal skin thickness, which is caused by increased collagen deposition, is thought to correlate with more severe internal organ involvement, morbidity, and mortality .…”
Section: Discussionmentioning
confidence: 97%
“…Akin to our finding of an association with more severe skin disease assessed by MRSS and more pronounced esophageal dysmotility (i.e., absent contractility), Vischio et al found a correlation between MRSS and abnormal esophageal transit scintigraphy. 35 Dermal skin thickness, which is caused by increased collagen deposition, is thought to correlate with more severe internal organ involvement, morbidity, and mortality. 34,[36][37][38] A study utilizing endoscopic ultrasound identified thickened (compared with normal controls) esophageal walls, mainly in the submucosa and muscularis, in 14 patients with dcSSc and 11 lcSSc, which also correlated with the presence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the possibility of indirect assessment of interstitial lung disease severity, based on the degree of esophageal stagnation [17]. Finally, scintigraphy, being a simple and non-invasive study, seems to be an optimal diagnostic technique for routine monitoring of esophageal disease progression, as suggested by Vischio et al [18]. …”
Section: Significance Of Esophageal Transit Study In Systemic Sclerosismentioning
confidence: 99%